Digital Transformation Strategy for Handicraft SMEs during the Covid-19 Pandemic in Gianyar Regency - Telagawathi, Ni Luh Wayan Sayang; Suci, Ni Made; Heryanda, Komang Krisna (International Journal of Social Science and Business, 2022)
One of the biggest challenges for MSMEs during the Covid-19 pandemic is to transform to digital technology. Some of the big challenges include: first, the level of digital ecosystem connectivity is still limited. This study aims to deepen the strategies carried out by woven handicraft SMEs in adapting to the digital world during the Covid-19 pandemic. Digital transformation for MSMEs is a necessity during the current pandemic, but it is also inseparable from the challenges that accompany it. The weaving handicraft UMKM players in particular have a strategy that must face various obstacles. One of the most important obstacles is the difficulty of adapting to digital technology, in this case online marketing in various forms. MSMEs are forced to design strategies to enter the digital ecosystem. This article argues that MSMEs will be tested for resilience in the midst of a crisis in order to exploit their resources and take innovative steps. This article makes the weaving craftsmen in Gianyar Regency the subject of research. The method of data collection is done by observation and in-depth interviews. Data classification and analysis were carried out using the principles of qualitative methods. The digital transformation strategy of weaving SMEs in this pandemic period is a necessity. Therefore, the only way is to adopt digital transformation. To respond to changes in people's behaviour due to physical and social restrictions, SMEs in weaving craft need to migrate from offline-based businesses to online-based channels.